DARI SOPHIA DAN SOPHOS (DARI KEBIJAKSANAAN DAN ORANG BIJAK SAMPAI AKAL-AKALAN) - Sudin Sudin (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2016)
Sophism is always connectedwith rethoric that give high value towards language's "effectiveness". Sharp consciousness to language's functions becomes a particular critic to ontological way of thinking that structuring language to the existence of something that being expressed. Sophism believes to the effectiveness oflanguage even could create an "existence" of something that according to common understanding "not exists". Therefore, Sophia is always contradicting to sophos.